IBN RUSYD MEETS RELIGION, PHILOSOPHY AND SCIENCE - adam gio amaliano (INNOVATIO: Journal for Religious Innovations Studies, 2022)
Ibn Rusyd is one of the philosophers who sought to combine religion and philosophy based on Islamic teachings, such as his belief that philosophy is not incompatible with Islam. Even Muslims are required to study it or are encouraged to do so. This research seeks to learn about Ibn Rusyd's efforts in bringing religion, philosophy, and science together and the relevance of Ibn Rusyd's thinking in bringing religion, philosophy, and science together in modern life. The writer uses content analysis, a research method that employs procedures to draw valid conclusions from books and documents. An analysis of Ibn Rusyd's thoughts on harmonizing religion, philosophy, and science, by making a justification classification based on the capacity of Muslim religious understanding will substantially prove a point. Because basically, one's understanding of religion at a certain level will not be separated from the function of reason as a promoter of rational thought. Without reason, one will not be able to accept the truth of religion, even if it is at a low "rational" level. This shows that the relationship between rational truth and religion will never be contradictory. What can be contradictory is human understanding of the contents of revelation. Abstrak: Ibnu Rusyd merupakan salah satu tokoh filsuf yang berupaya menggabungkan antara agama dan filsafat dengan berlandaskan prinsip-prinsip ajaran Islam, seperti pendapat beliau bahwa filsafat tidaklah bertentangan dengan islam, bahkan orang islam diwajibkan atau sekurang-kurangnya dianjurkan untuk mempelajarinya. Penelitian ini ingin mengetahui upaya-upaya Ibn Rusyd dalam mempertemukan agama, filsafat dan sains serta ingin mengetahui relevansi pemikiran Ibn Rusyd mempertemukan agama, filsafat dan sains dalam kehidupan sekarang. Metode yang digunakan adalah content analysis yaitu metode penelitian yang memanfaatkan seperangkat prosedur untuk menarik kesimpulan yang sahih dari sebuah buku dan dokumen. Analisis terhadap pemikiran-pemikiran Ibn Rusyd dalam menyelaraskan agama, filsafat, dan sains, dengan cara membuat klasifikasi pembenaran berdasarkan tingkatan kapasitas pemahaman keagamaan kaum Muslimīn, secara substansial akan menemukan titik simpul. Karena pada dasarnya, pemahaman seseorang terhadap agama pada tingkatan tertentu tidak akan terlepas dari fungsi akal yang sebagai promotor suatu pemikiran yang rasional. Tanpa akal seseorang tidak akan dapat menerima kebenaran agama, meskipun dalam tingkatan “rasional” yang rendah. Hal ini menunjukkan bahwa hubungan kebenaran rasio dan agama tidak akan pernah bertentangan, yang bisa bertentangan adalah pemahaman manusia terhadap isi kandungan yang di bawa oleh wahyu. Kata Kunci: Ibn Rusyd, Agama, Filsafat dan Sains